Some observations on the signs of certain death in the 18th century - Gorini, Ilaria; Martini, Mariano; Licata, Marta (Acta Biomedica Atenei Parmensis, 2018)
In 1783, the work of Ferdinand de la Boissiere, Letters above the certainty of death signs with various observations and experiences over the drowned, was published in Rome. Manuscript is a translation of the French work of Antoine Louis, Lettres sur la certitude des signes de la mort, printed in France in 1752 and in which the surgeon discussed on the certain diagnosis of death. The Louis’s work represented an important contribute of medicine especially because in the 18th century only the appearance of the first putrefactive processes was recognized as the indisputable sign of death. In the debate of the time, the treaty of Antoine Louis (1723-1792) overtaken the believed that the only indisputable sign of death was the appearance the first putrefaction processes. Our paper is limit to offering some author’s account around the characteristic signs of death, which dispense from putrefaction of the bodies or the rigidity of the limbs and the collapse and softness of the eye. The book boasted a great meaning in the medical association of the time, especially because it discussed with contemporary criteria the signs of certain death.